Amendements on Salinity and Water Retention of Sand Base Rootzone and Turfgrass Yield - Rahayu Rahayu; Yang Geun Mo; Choi Joon Soo (Sains Tanah: Journal of Soil Science and Agroclimatology, 2019)
This research was column pot experiment with turfgrass was Kentucky bluegrass (Poa pratensis) plant irrigated saline irrigation and the column soaked in saline water. Rootzone profile consisted of 20 cm using saline lake dredged up sand. The sand amendments of the root zone were soil, zeolite, bottom ash, and peat. The mixtures of topsoil were; 90% sand + 10% peat moss, 80% sand + 10% soil + 10 % bottom ash, 80% sand + 20% soil, 90% sand + 5% peat + 5% zeolite, and 80% sand + 20% bottom ash. Interruption layer with coarse sand with diameters over 2 mm of 20 cm and 10 cm loamy soil as the bottom layer of the column. The result showed that Kentucky bluegrass could grow in sand based growing media amended by peat, sandy loam soils, bottom ash and zeolite being irrigated by 2 dS m-1 saline water. Sand-based growing media amended by peat resulted in the highest clipping weigh but showed the highest salt accumulations. Sand amended by bottom ash and applied gypsum decreased clipping weigh, decreased SAR and increased calcium (Ca) when compared to the soil + peat (SP).  Sand amended by zeolite and gypsum decreased clipping weight, decreased sodium adsorption ratio (SAR) and higher Ca. Higher soil moisture retention of growing media promoted the growth of Kentucky bluegrass in spring, and lower moisture content promoted the growth in summer and fall season.